Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/andr.12485
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of hematocrit in gender‐affirming hormone treatment: results from European Network for the Investigation of Gender Incongruence

Abstract: In trans persons on gender-affirming hormonal treatment, a decrease (in trans women) or increase (in trans men) in hematocrit is often observed. Reference ranges for evaluation of hematocrit levels in trans persons have not been established. This prospective cohort study is part of the European Network for the Investigation of Gender Incongruence (ENIGI). At the Ghent and Amsterdam sites, we included 625 hormone-naïve trans persons. Gender-affirming hormonal treatment was initiated at the first visit. In trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 45 publications
7
74
2
3
Order By: Relevance
“…This gender difference could simply be due to the lower AAS doses used by women. However, when supra‐physiological doses of testosterone were given to transgender men, hematocrits higher than 50% were rarely found . Thus, hematological biomarkers for AAS use may be restricted to men using AAS.…”
Section: Discussionmentioning
confidence: 99%
“…This gender difference could simply be due to the lower AAS doses used by women. However, when supra‐physiological doses of testosterone were given to transgender men, hematocrits higher than 50% were rarely found . Thus, hematological biomarkers for AAS use may be restricted to men using AAS.…”
Section: Discussionmentioning
confidence: 99%
“…Both T formulations similarly led to an increase in haemoglobin and haematocrit although this always remained within the physiological range. It has been recently reported that transmen receiving TE had higher increases in serum haematocrit levels compared to transmen receiving TU and an explanation might be that short‐acting intramuscular injections cause a rapid supraphysiological peak shortly after injection . It is well known that androgens stimulate erythropoiesis .…”
Section: Discussionmentioning
confidence: 99%
“…In the hypogonadal men, TU has been associated with rare cases of pulmonary oil microembolism (1.5 per 10 000 injections) . TE, on the other hand, requires frequent injections resulting in peaks and troughs in T levels that may have consequences on mood and various health parameters, in particular on the rate of erythrocytosis which is higher in subjects receiving short‐acting intramuscular injections . We reported that in the short term—1 year—short and long‐acting T formulations perform equally in terms of efficacy and safety in transmen subjects .…”
Section: Introductionmentioning
confidence: 97%
“…In a prospective study of transmen initiating hormone therapy, the hematocrit increased over the first 12 months of testosterone use, with the largest increase in the first 3 months. 57 Only 11.5% of transmen were found to have an increased hematocrit >50%, with a maximal hematocrit of 54% seen in 1 of 192 testosterone-treated patients. Increased BMI was associated with a hematocrit >50%; no differences in smoking or other risk factors were seen.…”
Section: Erythrocytosismentioning
confidence: 97%
“…Erythrocytosis is expected with the use of testosterone in transmen but a possible increase in thromboembolic risk is concerning. In a prospective study of transmen initiating hormone therapy, the hematocrit increased over the first 12 months of testosterone use, with the largest increase in the first 3 months . Only 11.5% of transmen were found to have an increased hematocrit >50%, with a maximal hematocrit of 54% seen in 1 of 192 testosterone‐treated patients.…”
Section: Case Iii: Ftmmentioning
confidence: 99%